2020
DOI: 10.1016/j.ijcha.2020.100585
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and significance of isolated left ventricular non-compaction phenotype in normal black Africans using echocardiography

Abstract: Background Several large, prospective screening studies of predominantly Caucasian patients have suggested that hypertrabeculation may not necessarily be pathologic unless there is concomitant left ventricular (LV) dysfunction, LV dilatation, history of arrhythmia, family history, or characteristic gene mutations. This conundrum may be magnified in blacks, in whom hypertrabeculation and LV hypertrophy is more common. We therefore investigated the frequency of hypertrabeculation/isolated LV noncomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There is a clear association between symptomatic patients with abnormal echocardiographic findings and an impaired long-term clinical outcome. Previous reports described a noncompaction phenotype in pregnancy, athletes and other cardiac healthy individuals without functional impairment (30)(31)(32). In these patients, noncompaction is often reversible, does not affect cardiac function and is not associated with a CMP.…”
Section: Implications For Outcomementioning
confidence: 88%
“…There is a clear association between symptomatic patients with abnormal echocardiographic findings and an impaired long-term clinical outcome. Previous reports described a noncompaction phenotype in pregnancy, athletes and other cardiac healthy individuals without functional impairment (30)(31)(32). In these patients, noncompaction is often reversible, does not affect cardiac function and is not associated with a CMP.…”
Section: Implications For Outcomementioning
confidence: 88%
“…Among patients with left ventricular non-compaction (LVNC), echocardiography is often the first method that unmasks the pathognomonic prominent ventricular trabeculations with thick, bilayered myocardium and deep intertrabecular recesses. Nel et al [56] showed that although trabeculations may be considered as a normal variant in black Africans, utilizing the current diagnostic criteria enables differentiation of a possible LVNC phenotype. Normal individuals with hypertrabeculation have normal indices of systolic and diastolic left ventricular function.…”
Section: Cardiomyopathiesmentioning
confidence: 99%
“…Of major interest are results from CMR imaging studies, which detected the phenotype of LVNC in healthy athletes and pregnant women, suggesting a physiologic adaptation [19,20]. The same can be found in normal healthy persons, in parts depending on the ethnic group [11]. In this context, future research needs to unravel when the phenotype of LVNC represents pathologic remodeling and when it is a morphologic variant in a healthy person.…”
Section: Introductionmentioning
confidence: 98%
“…Initially, the term isolated NCCM was used for cases without congenital or other structural heart defects. Today, some groups use the term for cases with areas of LVNC and normal LV function [ 11 ]. Table 1 shows a selection of terms and abbreviations used for noncompaction cardiomyopathy and the noncompacted morphology in the last nearly 100 years.…”
Section: Introductionmentioning
confidence: 99%